1985
DOI: 10.1210/jcem-60-2-311
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-Stimulated Glucose Disposal Is not Increased in Anorexia Nervosa*

Abstract: Insulin-stimulated glucose disposal was investigated using the euglycemic hyperinsulinemic glucose clamp technique in six women with anorexia nervosa (27.3 +/- 4.9 yr old; weight, 38.8 +/- 6.6 kg) and compared to results obtained in six normal women (22.6 +/- 1.2 yr old; weight, 58 +/- 2.5 kg) and seven obese women (26.8 +/- 7.7 yr old; weight, 92.5 +/- 13.8 kg). The glucose clamp was performed for 2 h using the Biostator and a continuous insulin infusion of 100 mU kg-1 h-1. Plasma levels of insulin were deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

1988
1988
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…Lipid concentrations were comparable across plasma and serum, although, different laboratory methods were used. In the nine studies with unpecified diagnostic criteria (Blickle et al, 1984;Castillo et al, 1985;Crisp et al, 1968;Miyai et al, 1975;Mordasini et al, 1977;Nestel, 1974;Rigaud, 1999;Stephan et al, 1977;Uhe et al, 1992), the study participants had low BMIs (<16.3 kg/m 2 ), low percentage of ideal body weight (<73.8%), confirmation of the AN diagnosis by psychiatric examination, history of food aversion, secondary amenorrhea, and/or rapid (Umeki, 1988) In the nine studies with unpecified diagnostic criteria (Blickle et al, 1984;Castillo et al, 1985;Crisp et al, 1968;Miyai et al, 1975;Mordasini et al, 1977;Nestel, 1974;Rigaud, 1999;Stephan et al, 1977;Uhe et al, 1992), the study participants had low BMIs (<16.3 kg/m 2 ), low percentage of ideal body weight (<73.8%), confirmation of the AN diagnosis by psychiatric examination, history of food aversion, secondary amenorrhea, and/or rapid (Umeki, 1988) …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lipid concentrations were comparable across plasma and serum, although, different laboratory methods were used. In the nine studies with unpecified diagnostic criteria (Blickle et al, 1984;Castillo et al, 1985;Crisp et al, 1968;Miyai et al, 1975;Mordasini et al, 1977;Nestel, 1974;Rigaud, 1999;Stephan et al, 1977;Uhe et al, 1992), the study participants had low BMIs (<16.3 kg/m 2 ), low percentage of ideal body weight (<73.8%), confirmation of the AN diagnosis by psychiatric examination, history of food aversion, secondary amenorrhea, and/or rapid (Umeki, 1988) In the nine studies with unpecified diagnostic criteria (Blickle et al, 1984;Castillo et al, 1985;Crisp et al, 1968;Miyai et al, 1975;Mordasini et al, 1977;Nestel, 1974;Rigaud, 1999;Stephan et al, 1977;Uhe et al, 1992), the study participants had low BMIs (<16.3 kg/m 2 ), low percentage of ideal body weight (<73.8%), confirmation of the AN diagnosis by psychiatric examination, history of food aversion, secondary amenorrhea, and/or rapid (Umeki, 1988) …”
Section: Resultsmentioning
confidence: 99%
“…BMI was calculated from average weight and height (Castillo, Scheen, Lefebvre, & Luyckx, 1985;Mordasini, Klose, Heuck, Augustin, & Greten, 1977). BMI was calculated from average weight and height (Castillo, Scheen, Lefebvre, & Luyckx, 1985;Mordasini, Klose, Heuck, Augustin, & Greten, 1977).…”
Section: Meta-analysismentioning
confidence: 99%
“…In particular, insulin-stimulated glucose disposal has been reported to be normal (29), enhanced (30,31), or decreased (32) in AN subjects. In our study, we found a reduced insulin-stimulated glucose disposal in the AN group, with prevalent impairment of nonoxidative glucose metabolism and no difference in glucose oxidation, thus suggesting that insulin stimulates glucose oxidation more than glucose storage in AN patients.…”
Section: Discussionmentioning
confidence: 99%
“…The peripheral effects of insulin have been reported in¬ creased in anorectic patients (Mecklenburg et al 1974) and the present investigation may be in ac¬ cord with this report. Insulin sensitivity and in¬ sulin clearance in patients with anorexia nervosa have been imported to be both normal (Castillo et al 1985) and increased (Zuniga-Guajardo et al 1986). This discrepancy, as yet unclarified, is prob¬ ably due to differences of examination time and caloric intake.…”
Section: Discussionmentioning
confidence: 99%